Research Progress of TCM in the Treatment of Interstitial Lung Disease - Wang, Le; Li, Yaohui (Journal of Contemporary Medical Practice, 2025)
Interstitial lung disease (ILD) is a heterogeneous group of diseases. The most common clinical symptom of ILD is progressive exertional dyspnea, usually accompanied by cough, fatigue, etc. Physical examination showed shallow and rapid breathing, significant burst sounds in the lower lungs, cyanosis of lips and fingers, and clubbing fingers (toes). Pulmonary hypertension and pulmonary heart disease can occur in the late stage, which is a kind of refractory disease in clinic. There are some problems in modern medical treatment, such as limited curative effect and significant side effects. Based on the principles of ‘holistic view’ and ‘syndrome differentiation and treatment’, traditional Chinese medicine shows unique advantages by regulating the function of viscera and improving the airway microenvironment. This paper systematically summarizes the research on the theoretical characteristics and treatment ideas of interstitial lung disease by various doctors of traditional Chinese medicine in the past five years, and discusses the future development direction in combination with the application of clinical and cutting-edge technology, so as to provide reference for clinical practice and research.